CASH FLOW PROYEK DENGAN SUMBER MODAL BANK SYARIAH PADA PEMBANGUNAN DAN REHABILITASI GEDUNG PELAYANAN KESEHATAN PEMERINTAH KABUPATEN GUNUNG KIDUL - Vendie Abma; Fitri Nugraheni; Metalindra Metalindra (Politeknik Negeri Jakarta, 2020)
A construction project has several factors that affect the success of a project. One of the factors was an optimal project’s cash flow. Optimizing cash flow of a construction project can be done by making several cash flow plans, and choosing the best one considering appropriate project’s time and cost constraints. The purpose of this study is to obtain an optimal cash flow plan on a construction project using a capital loan from Sharia Bank. This research will be carried out on a specific project which is Construction and Rehabilitation Project of Government Health Service Building, District of Gunungkidul. In this study, the method used to analyze data is to make several project cash flow based on “Earliest Start” scheme by determining the duration for each activity and creating a network diagram using the Precedence Diagram Method (PDM). The final step is analysing the cash flow by calculating negative overdraft for each cash flow plan to determine the amount of capital loan from Sharia Bank and then comparing profits to obtain the optimal one. Analysis and discussion reveal that on the system of given Down Payment, and Project’s Termyn 50%, 75% and 100%, and a loan from Sharia Bank it is found that the optimum cash flow will make profit of 7.49%. Keywords: Cash Flow, Earliest Start (ES), Optimal Profit, Sharia Bank.